Vocabulary Enrichment and Student’ Communicative Competence: The Case in Task-Based Language Teaching - Widanta, I Made Rai Jaya (Universitas Pendidikan Ganesha, 2023)
In order to realize and support Indonesian national educational program of MBKM, every higher educational institution is recommended and stimulated to implement learning model of task-based language teaching (TBLT). This study investigated how enriching vocabularies and giving other prompt such as driving question words effective for students’ speaking performance, such as fluency. This was a qualitatively designed study. One class semester two students majoring in civil engineering department were involved as research participants. Learning material in the form of snapshot consisting of pictures was design to bridge the students thought to the whole learning materials. Snapshot without vocabulary enrichment and driving questions was tried in the first two sessions. Discussion upon the lesson was intensively undertaken to know why students hesitated and were doubtful to speak. Observation results combined with students’ perception concluded that enrichment of vocabularies and stimulating questions were found effective to increase students’ speaking performance, learning motivation and enthusiasm. Moreover, by practicing in front of their group and by succeeding in perform such task made them more stimulated to do better. Therefor made their learning meaningful.